Arterial function should be focused in the follow-up treatment of COVID-19 mild patients - Jinbo Liu; Jie Chen; Hongyu Wang (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2021)
An outbreak of pneumonia named coronavirus disease 2019 (COVID-19) occurred in Wuhan in December 2019. COVID-19 has spread rapidly throughout China, even the whole world [1]. The treatment of COVID-19 has won a stage of success after the active intervention of the Chinese government. Cardiovascular damage was found in COVID-19 patients with the increasing research of COVID-19. There might be two pathways [2,3].